TINJAUAN HUKUM EKONOMI SYARIAH TENTANG PENETAPAN HARGA DALAM JUAL BELI HEWAN TERNAK SAPI INSEMINASI BUATAN DI DESA SUNTENJAYA KECAMATAN LEMBANG KABUPATEN BANDUNG BARAT - Rismayanti, R; K, Mustofa (Al-Muamalat: Jurnal Ekonomi Syariah, 2019)
ABSTRACT Artificial insemination (IB) is a marital process carried out by human intervention, which is to bring together sperm and egg cells so that fertilization can occur. Artificial insemination technology that is increasingly developing causes the growing interest of the community in the technology and then produced until sold. buying and selling itself is one of muamalah activities that brings together sellers and buyers by reaching a mutual agreement on goods that are traded or can be interpreted as the exchange of an item with other goods or money with goods or otherwise with certain conditions. In buying and selling is closely related to pricing. The legal pricing can be as long as it is not wrong and harms others. The problem in this study is the occurrence of pricing determined by the seller unilaterally by means of not following the market mechanism. The purpose of this journal writing is to find out the background of buying and selling of artificial insemination cattle, to find out the price fixing process in artificial insemination cattle and to find out how the Sharia Economic Law reviews the pricing system in buying and selling livestock artificial cow insemination. This research comes from the idea that in Sharia Economic Law in setting prices is limiting profits or fixing prices by not harming the consumers and determining the price standards according to healthy market conditions. The research method used is an empirical juridical method. Data sources in this study are primary data sources obtained from sellers and buyers. While secondary sources are obtained from the literature, certain parts of books, papers, fiqh books and others. Based on the results of field research data shows that the Review of Sharia Economic Law on the system of pricing in buying and selling artificial insemination cattle based on Ibnu Khaldun's opinion that the pricing that occurred in Suntenjaya Village, Lembang District, West Bandung Regency, cannot be said to be in accordance with Islamic law because even though initially there is a valid contract process between the two parties, namely the buyer and seller, but in terms of price fixing, only one party is allowed to determine the seller without referring to the market price determined by Bandung Regency Regional Regulation Number 21 of 2011 concerning Regional Business Production Sales Levy Field of Livestock and Fisheries of Bandung Regency Article 1 Paragraphs 24 and 25.